Low, but Not High, Pulsating Fluid Shear Stress Affects Matrix Extracellular Phosphoglycoprotein Expression, Mainly via Integrin β Subunits in Pre-Osteoblasts - Jianfeng Jin; Behrouz Zandieh-Doulabi (Current Issues in Molecular Biology)
Matrix extracellular phosphoglycoprotein (Mepe), present in bone and dentin, plays important multifunctional roles in cell signaling, bone mineralization, and phosphate homeostasis. Mepe expression in bone cells changes in response to pulsating fluid shear stress (PFSS), which is transmitted into cells through integrin-based adhesion sites, i.e., α and β subunits. Whether and to what extent PFSS influences Mepe expression through the modulation of integrin α and/or β subunit expression in pre-osteoblasts is uncertain. Therefore, we aimed to test whether low and/or high PFSS affects Mepe expression via modulation of integrin α and/or β subunit expression. MC3T3-E1 pre-osteoblasts were treated with ± 1 h PFSS (magnitude: 0.3 Pa (low PFSS) or 0.7 Pa (high PFSS); frequency: 1 Hz). Single integrin fluorescence intensity in pre-osteoblasts was increased, but single integrin area was decreased by low and high PFSS. Expression of two integrin α subunit-related genes (Itga1 and Itga5 2) was increased by low PFSS, and one (Itga5 2) by high PFSS. Expression of five integrin β subunit genes (Itgb1, Itgb3, Itgb5, Itgb5 13, and Itgb5 123) was increased by low PFSS, and three (Itgb5, Itgb5 13, and Itgb5 123) by high PFSS. Interestingly, Mepe expression in pre-osteoblasts was only modulated by low, but not high, PFSS. In conclusion, both low and high PFSS affected integrin α and β subunit expression in pre-osteoblasts, while integrin β subunit expression was more altered by low PFSS. Importantly, Mepe gene expression was only affected by low PFSS. These results might explain the different ways that Mepe-induced changes in pre-osteoblast mechanosensitivity may drive signaling pathways of bone cell function at low or high impact loading. These findings might have physiological and biomedical implications and require future research specifically addressing the precise role of integrin α or β subunits and Mepe during dynamic loading in bone health and disease.